The deleterious effects of smoking resumption after heart transplantation. Issue 9 (19th November 2021) - Vorlat, Anne; Even, Pjotr; Devrieze, Ylonka; Buyens, Ellis; Vermeulen, Tom; Rodrigus, Inez; Heidbuchel, Hein; Claeys, Marc
Abstract: Aims: Smoking is linked to disease and survival in the general and transplant population. We studied the smoking history, disease and survival of patients after heart transplantation. Methods: A total of 130 patients who underwent heart transplantation between 1995 and 2019 received a questionnaire to document their smoking history. We assessed patient characteristics, comorbidities and survival. Results: Sixty-five per cent of patients were active or former smokers prior to heart transplantation. All patients stopped smoking; 26% of the former smokers resumed smoking after transplantation. Patients who resumed smoking were younger at the time of transplantation, used fewer statins and were more likely to be treated with azathioprine after transplantation. The mean follow-up for all patients was 11 ± 5.5 years. Patients who resumed smoking were more likely to develop solid organ cancers (45%) compared to those who remained abstinent (23%) and those who never smoked (13%) ( p 0.014). A Cox proportional hazards regression analysis identified smoking resumption, with a RR of 2.31 (1.14–4.68, p 0.02), and age at transplantation, with a RR of 1.03 (1–1.06, p 0.034), as significant for survival. Patients resuming smoking after transplantation had a significantly higher risk of dying from solid organ cancer, with a RR of 2.54 (1.03, 6.28; p 0.04) with a short median survival time (25th–75th percentile) of (1 (0–5) months, p 0.007). Conclusion: Patients who resume smoking after heart transplantation have worse survival and are at higher risk of dying from solid organ cancer. Implementing a smoking cessation plan throughout the post-transplant period is important.